La educación para el amor y la sexualidad y su incidencia en los estudiantes de séptimo año de la escuela “Carlota Jaramillo”. cantón La Maná, periodo lectivo 2011- 2012 - Tubón Macías, Esther Genoveva (2012)
This research aims to design a training program in sex education to guide the educational community in the field of education for love and sexuality on the students of the seventh year of the school "Carlota Jaramillo", where it was observed that not exist an adequate planning to guide children in sex education as well that it does not have a good program to provide knowledge of this subject on this area. It was used descriptive research based on method field….